A cross-language comparison of pitch patterns in declarative questions and statements. (1st September 2013) - Lin, Emily; Daniell, Paul; Al Busaidi, Salma
Abstract : This preliminary study investigated the acoustic differences between declarative questions and statements in two non-tonal languages (Arabic and English) and two tonal languages (Mandarin and Taiwanese). All participants read 28 English phrases in two sentence types: declarative question and statement. The non-native English speakers also read the phrases translated in their native languages. Acoustic measures derived from these sentences included measures of fundamental frequency (F0) and intensity. Results from multiple analysis of variance revealed that declarative questions, compared to statements, had significantly higher F0 and intensity regardless of language and speaker's nativeness. In addition, the F0 of a statement was found to be a strong predictor for that of the corresponding question in both non-tonal and tonal languages.